Taxation of carbon emissions with social and private discount rates - Mathias Mier; Jacqueline Adelowo (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Energy system and power market models refrain from distinguishing between private and social discount rates. We devise a strategy to account for diverging private and social discount rates in intertemporal optimization frameworks, resulting in an optimal carbon tax above the marginal damage when private discount rates exceed the social one. We quantify results for the European power market until 2050. Not distinguishing between private and social discount rates yields carbon emissions of 0.83 Gt in 2050 with rising trend from 2020 onwards. Distinguishing between private and social discount rates achieves full decarbonization (-0.15 Gt in 2050) and avoids damages of 1,386 billion exteuro until 2050. Results explain missing investments of firms and suggest that policymakers should announce high future carbon prices to incentivize sufficient investments into clean technologies.
Keywords: C61; H21; H23; H43; L94; 330; Carbon taxation; discounting; social cost; carbon emission; externality; intertemporal optimization; power market model; decarbonization